Climate change impedes scleractinian corals as primary reef ecosystem engineers - Wild, Christian; Hoegh-Guldberg, Ove; Naumann, Malik S.; Colombo-Pallotta, M. Florencia; Ateweberhan, Mebrahtu; Fitt, William K.; Iglesias-Prieto, Roberto; Palmer, Caroline; Bythell, John C.; Ortiz, Juan-Carlos; Loya, Yossi; van Woesik, Robert (Marine and Freshwater Research, 2011)
Coral reefs are among the most diverse and productive ecosystems on our planet. Scleractinian corals function as the primary reef ecosystem engineers, constructing the framework that serves as a habitat for all other coral reef-associated organisms. However, the coral’s engineering role is particularly susceptible to global climate change. Ocean warming can cause extensive mass coral bleaching, which triggers dysfunction of major engineering processes. Sub-lethal bleaching results in the reduction of both primary productivity and coral calcification. This may lead to changes in the release of organic and inorganic products, thereby altering critical biogeochemical and recycling processes in reef ecosystems. Thermal stress-induced bleaching and subsequent coral mortality, along with ocean acidification, further lead to long-term shifts in benthic community structure, changes in topographic reef complexity, and the modification of reef functioning. Such shifts may cause negative feedback loops and further modification of coral-derived inorganic and organic products. This review emphasises the critical role of scleractinian corals as reef ecosystem engineers and highlights the control of corals over key reef ecosystem goods and services, including high biodiversity, coastal protection, fishing, and tourism. Thus, climate change by impeding coral ecosystem engineers will impair the ecosystem functioning of entire reefs.